Overexpression of the autism candidate gene Cyfip1 pathologically enhances olivo-cerebellar signaling in mice - Busch, Silas E.; Simmons, Dana H.; Gama, Eric; Du, Xiaofei; Longo, Francesco; Gomez, Christopher M.; Klann, Eric; Hansel, Christian (Frontiers in Cellular Neuroscience, 2023)
Cyfip1, the gene encoding cytoplasmic FMR1 interacting protein 1, has been of interest as an autism candidate gene for years. A potential role in autism spectrum disorder (ASD) is suggested by its location on human chromosome 15q11-13, an instable region that gives rise to a variety of copy number variations associated with syndromic autism. In addition, the CYFIP1 protein acts as a binding partner to Fragile X Messenger Ribonucleoprotein (FMRP) in the regulation of translation initiation. Mutation of FMR1, the gene encoding FMRP, causes Fragile X syndrome, another form of syndromic autism. Here, in mice overexpressing CYFIP1, we study response properties of cerebellar Purkinje cells to activity of the climbing fiber input that originates from the inferior olive and provides an instructive signal in sensorimotor input analysis and plasticity. We find that CYFIP1 overexpression results in enhanced localization of the synaptic organizer neurexin 1 (NRXN1) at climbing fiber synaptic input sites on Purkinje cell primary dendrites and concomitant enhanced climbing fiber synaptic transmission (CF-EPSCs) measured using whole-cell patch-clamp recordings from Purkinje cells in vitro. Moreover, using two-photon measurements of GCaMP6f-encoded climbing fiber signals in Purkinje cells of intact mice, we observe enhanced responses to air puff stimuli applied to the whisker field. These findings resemble our previous phenotypic observations in a mouse model for the human 15q11-13 duplication, which does not extend to the Cyfip1 locus. Thus, our study demonstrates that CYFIP1 overexpression shares a limited set of olivo-cerebellar phenotypes as those resulting from an increased number of copies of nonoverlapping genes located on chromosome 15q11-13.